Antimicrobial activity of aqueous extracts and of berberine isolated from Berberis heterophylla - Freile, M L (2003)
Fil: Freile, M. L. Universidad Nacional de la Patagonia San Juan Bosco. Facultad de Ciencias Naturales; Chubut, Argentina.